Video Analysis and Repackaging for Distance Education - Ram, A. Ranjith; Chaudhuri, Subhasis; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
None
Media for Distance Education -- Instructional Media Repackaging -- Current State of the Art -- Preprocessing of Lecture Videos -- Video Content Re-creation -- Display of Media on Miniature Devices -- Copyright Protection -- Lecture Video Capsule for Course Preview -- Conclusions and Future Directions of Research -- Appendices -- References -- Index.
Keywords: Computer science; Computer vision; Computer Science; Image Processing and Computer Vision; Signal, Image and Speech Processing; Education (general).